2011
DOI: 10.21307/ijssis-2017-453
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Sensor Platform for Autonomous Sensing in Automotive Applications

Abstract: Abstract-This paper presents the development of a versatile sensor platform used for autonomous data acquisition. The key advantages of the platform are its compact design, implemented onboard sensors, standard interfaces to connect application specific sensors and subsequently simple installation and low costs for the preparation of a measurement task. The paper provides details of the platform design and key characteristics. Practical exemplary applications in the field of automotive sensing, covering therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Simple systems generally use only a single sensor, fixed task. However for the intelligent system and autonomous system, people found that a single sensor cannot satisfy the need of target recognition, and operating environment, especially in the uncertain environment [11]. In this paper, a low power and minimally intrusive multi sensor network has been developed for health monitoring of elderly people.…”
Section: Introductionmentioning
confidence: 99%
“…Simple systems generally use only a single sensor, fixed task. However for the intelligent system and autonomous system, people found that a single sensor cannot satisfy the need of target recognition, and operating environment, especially in the uncertain environment [11]. In this paper, a low power and minimally intrusive multi sensor network has been developed for health monitoring of elderly people.…”
Section: Introductionmentioning
confidence: 99%
“…To implement a pleasing management, the system should acquire the working current and terminal voltage of the traction battery systems very accurately [1][2][3][4]. The accuracy of the voltage and current measurements affects several aspects of the energy management, and one of the most critical parts is the SOC calculation of the traction battery.…”
Section: Introductionmentioning
confidence: 99%
“…One of the very different tasks of the development of EVs, comparing with the traditional inner combustion vehicles, is the energy management system, which takes charge of the power coordinating between the driving system and the electric power supplies. To implement a pleasing management, the system should acquire the working current and terminal voltage of the traction battery systems very accurately [1][2][3][4]. The accuracy of the voltage and current measurements affects several aspects of the energy management, and one of the most critical parts is the SOC calculation of the traction battery.…”
Section: Introductionmentioning
confidence: 99%